Histone demethylase Jmjd3 modulates osteoblast apoptosis induced by tumor necrosis factor-alpha through directly targeting RASSF5. (1st November 2020) - Sun, Hai-Yan; Yang, Di; Mi, Jing; Yu, Ya-Qiong; Qiu, Li-Hong
ABSTRACT: Purpose : Regulation of gene expression is fine-tuned by a dynamic equilibrium between repressive modifications and transcriptional activation of histone tails. Jumonji domain-containing 3 (Jmjd3), also known as KDM6B, is a specific histone demethylase for trimethylation on histone H3 lysine 27 (H3K27me3) that specifically removes the methylation of H3K27me3 and promotes gene expression. Our previous study showed that Jmjd3 inhibits serum deprivation-induced osteoblast apoptosis. In this study, we clarified the role of Jmjd3 in tumor necrosis factor-alpha (TNF-α)-induced osteoblast apoptosis. Materials and Methods : Jmjd3 activity was inhibited by GSK-J4. Transfection of osteoblastic murine MC3T3-E1 cells with short hairpin RNA (shRNA) was used to establish stable Jmjd3 knockdown cells. Osteoblast apoptosis was detected using Annexin V-APC/PI staining, cysteinyl aspartate specific protease-3 (caspase-3) activity assays, and Western blot. Real-time polymerase chain reaction (PCR) and chromatin immunoprecipitation (ChIP) assays were performed to clarify the mechanism responsible for Jmjd3-regulated osteoblast apoptosis induced by TNF-α. Results : Based on Annexin V-APC/PI staining, caspase-3 activation, and poly ADP-ribose polymerase (PARP) cleavage, pretreatment with GSK-J4 and knockdown of Jmjd3 by shRNA transfection each inhibited osteoblast apoptosis. Furthermore, knockdown of Jmjd3 decreased the expression of Ras association domain family 5 (RASSF5), which is a pro-apoptotic gene of the Ras associated domain family. H3K27me3 levels in the promoter region of RASSF5 were up-regulated in the Jmjd3 knockdown cells. Conclusions : Jmjd3 regulated TNF-α-induced osteoblast apoptosis by targeting RASSF5.